Modern Broadcasting: Leveraging Artificial Intelligence and Big Data for More Personalized Content - Azahra, Astrid Sulistya; binti Abdullah Suhaimi, Nurnisaa; Yuningsih, Siti Hadiaty (International Journal of Linguistics, Communication, and Broadcasting, 2024)
Artificial intelligence (AI) technology and big data analytics have changed the landscape of the modern broadcast industry by providing a deeper understanding of audiences, increasing content personalization and strengthening engagement with viewers. In this study, we investigate the impact of the use of this technology in the broadcasting industry, with a focus on the analysis of demographic data, the use of recommendation algorithms, personalized interactions through AI technology, and optimization of broadcast time. Analysis of demographic data allows broadcasters to understand their audiences better, while the use of recommendation algorithms provides the opportunity to serve more personalized content to audiences, increasing engagement and interaction. The use of AI technology in audience interactions, such as chatbots and virtual assistants, also provides viewers with a more personalized experience, while optimizing broadcast time allows broadcasters to reach a wider audience and increase broadcast effectiveness. Although AI technology and big data analysis bring significant benefits, ethical challenges related to data privacy and security remain a major concern. By considering these challenges, broadcasters can leverage this technology effectively to improve content quality, increase engagement with audiences, and remain relevant in an ever-changing broadcast environment.